Genotype by environment effects on potato mini-tuber seed production in an aeroponics system - Mateus-Rodriguez, J.; Haan, Stef de; Rodríguez Delfin, A. (MDPI, 2014)
In order to evaluate the environmental effect on plant development and mini-tuber production of a diverse group of potato genotypes grown under an aeroponic system, a G × E interaction experiment was carried out in greenhouses located at CIP’s experimental stations in La Molina (Lima) and Huancayo (Junín). Five contrasting environments were set-up and evaluated. A combined Analysis of Variance was performed for the variables “days to tuber set”, “days to senescence” and “plant height”. An Additive Main Effects and Multiplicative Interaction (AMMI) Analysis was performed for yield variables: mini-tuber “weight” and “number of mini-tubers” per plant. There was a high variation in all the responses to the treatments. “Days to tuber set” was influenced by genetic responses, temperature and greenhouse Photosynthetically Active Radiation intensity. Considerable increases in the length of the vegetative cycle and plant height were recorded for all genotypes, and these were particularly notable in the warmer coastal environments. AMMI analysis showed that yield variables were primarily influenced by the genotypic effect followed by the genotype by environment interaction effect. The Venturana variety (T2) was the best performing genotype with a total average mini-tuber “weight” of 644 g per plant while the Chucmarina variety (T1) performed best for the variable “number of mini-tubers” with an overall average of 60.2 mini-tubers per plant. Both showed stability across different environments for these variables. The advanced clones T3 (395434.1), T5 (397077.16) and T6 (397073.16) showed stability for yield variables, but their performance was below the overall average of the trial. It is recommended that the environment and management should ideally be tailored to the genotype as this will result in significant yield gains.